The impact of ultra-processed foods and unprocessed or minimally processed foods on the quality of life among adolescents: a longitudinal study from China - Yang, Yuke; Gao, Yan; Yi, Xiangren; Hu, Yining; Zhao, Liangyu; Chen, Lu; Sui, Wenze; Zhang, Shuoqin; Ma, Sen (Frontiers in Nutrition, 2024)
The purpose of this study was to explore the associations between ultra-processed foods (UPF), unprocessed or minimally processed foods (UMFs) with the quality of life (QoL) in Chinese adolescents. The study included a baseline survey in 2021 (T1) and a follow-up survey in 2022 (T2), with a total of 3,206 participants, including 1,510 males (Age ± SE: 13.62±1.69) and 1,696 females (Age ± SE: 14.09±1.85). QoL was measured using the Quality of Life Scale for Children and Adolescents. All adolescents were asked to recall the foods they had eaten in the past week, which was classified using the NOVA system. Instant noodles, sugary drinks, and fried foods had a negative impact on adolescents' QoL. Snacks or desserts only had a negative impact on the girls' QoL. However, processed meats had a positive impact on the QoL of all adolescents. Fast food was beneficial for girls' QoL. Fruits had a positive impact on the QoL of all adolescents. Green leafy vegetables, red and orange vegetables, fish, shrimp, or other seafood had a positive impact on the QoL of girls. Fresh poultry, pork, beef, and other meats had a positive impact on boys' QoL. Soy products were detrimental to girls' QoL. Tubers had a negative impact on boys' QoL. Potatoes had a negative effect on the all adolescents' QoL. This study further expands the understanding of the relationship between UPF, UMFs, and QoL. It provides new insights and evidence for improving the QoL of adolescents.